Development of Trans-Free Fat by Interesterification - A, Rohit; Shelar, Dhaval N; Sahoo, Akshay Kumar; Patil, Shital A; S, Iranna (Journal of Postharvest Technology, 2022)
THis research focuses on the development of trans-fat-free margarine to improve puff pastry  quality while addressing health concerns. Extensive raw material analysis guided formulation,  encompassing fatty acid composition, chemical attributes, color profiles, and flour characteristics.  Central to the study was the interesterification process, enhancing shelf stability through vacuum  drying, and employing sodium methoxide and citric acid for homogeneity, safety, and palatability.  Bleaching elevated margarine quality. Comparing non-interesterified and interesterified margarine, peroxide values (2.47 vs. 0.99 meq/kg)  and trans fatty acid content (1.81% vs. 0.21%) demonstrated a positive impact of interesterification.  The application of the trans-fat-free margarine in puff pastry production revealed sensory preference  for the interesterified version, boasting superior texture and flavor stability. In conclusion, this study successfully developed trans-fat-free margarine, optimizing parameters  and enhancing its quality. This research contributes to healthier food choices, meeting consumer  demand, and improving sensory quality and puff pastry stability.
Keywords: Trans-fat-free; interesterification; vacuum drying.